Nano Fe and Mg2Ni derived from TMA-TM (TM = Fe, Ni) MOFs as synergetic catalysts for hydrogen storage in MgH2. Issue 5 (10th March 2020) - Ma, Zhewen; Zhang, Qiuyu; Zhu, Wen; Khan, Darvaish; Hu, Chuanzhu; Huang, Tianping; Ding, Wenjiang; Zou, Jianxin
Abstract : In situ generated Mg2 NiH4 /Mg2 Ni and α-Fe work as synergetic catalysts to improve the hydrogen sorption behaviors of the MgH2 /Mg system. Abstract : TMA-TM (TM = Fe, Ni) MOFs were synthesized successfully by a facile method. A MgH2 -TM MOF (TM = Fe, Ni) composite was obtained via ball milling and the corresponding hydrogen storage performance was investigated. Particularly, high-resolution transmission electron microscopy was performed to in situ characterize the dehydrogenation behavior of the MgH2 -TM MOF composite. The results reveal that nano α-Fe and Mg2 NiH4 /Mg2 Ni derived from the TMA-TM MOFs display a synergetic improving effect on the de/hydrogenation of MgH2 . During the hydrogen desorption process, Mg2 NiH4 /Mg2 Ni works as a "hydrogen pump" to quickly deliver hydrogen and facilitates hydrogen diffusion. Meanwhile, α-Fe accelerates the nucleation and growth of Mg by reducing the nucleation energy of Mg from MgH2 . The hydriding activation energy of the MgH2 -TM MOF declines to 45.3 kJ mol −1 H2 . Meanwhile, the peak dehydriding temperature of the MgH2 -TM MOF is 530.9 K, which is much lower compared with the MgH2 –Fe MOF composite (541.7 K) and as-milled MgH2 (685.2 K). Therefore, nano Mg2 Ni and α-Fe derived from the TMA-TM MOFs can remarkably improve the hydrogen storage properties of the MgH2 /Mg system due to their synergetic catalytic effects.